Effect of vitamin D supplementation on bone healing in patients with avascular necrosis of the hip: a narrative review - Alexander, Brytsko; Gennadiy, Koshman; Direcksze, Naveen D. K. N.; Yohanathan, Narendiran; Dassanayake, D. M. N. P. K. (International Journal of Research in Orthopaedics, 2026)
Vitamin D has been widely known for its role in maintenance and repair of skeletal system, where vitamin D deficiency (VDD) led to hindered effect on bone healing after fractures, bone defects and osteon formation in implants. Some studies have shown that increasing serum Vitamin D levels requires a significant period of time after the application of vitamin D for VDD. In addition, VDD at the time of bone (mainly hip) fracture is associated with an inflammatory response after the fracture. Avascular necrosis (AVN) is a serious complication of defective bone healing. VDD may be a potential risk factor for this incidence; however, further studies are required to validate this aspect in orthopedics. The crucial role of vitamin D in upregulating vascular endothelial growth factor on the proliferation of type-H vessels connects osteogenesis and angiogenesis pathways, thereby providing insight into how to tackle AVN. The primary aim of this review is to highlight the importance of vitamin D supplementation in patients with AVN during the bone regeneration phase.